Caprylic Triglyceride as a Novel Therapeutic Approach to Effectively Improve the Performance and Attenuate the Symptoms Due to the Motor Neuron Loss in ALS Disease - Zhao, Wei; Varghese, Merina; Vempati, Prashant; Dzhun, Anastasiya; Cheng, Alice; Wang, Jun; Lange, Dale; Bilski, Amanda; Faravelli, Irene; Pasinetti, Giulio Maria (PLOS ONE, 2012)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder of motor neurons causing progressive muscle weakness, paralysis, and finally death. ALS patients suffer from asthenia and their progressive weakness negatively impacts quality of life, limiting their daily activities. They have impaired energy balance linked to lower activity of mitochondrial electron transport chain enzymes in ALS spinal cord, suggesting that improving mitochondrial function may present a therapeutic approach for ALS. When fed a ketogenic diet, the G93A ALS mouse shows a significant increase in serum ketones as well as a significantly slower progression of weakness and lower mortality rate. In this study, we treated SOD1-G93A mice with caprylic triglyceride, a medium chain triglyceride that is metabolized into ketone bodies and can serve as an alternate energy substrate for neuronal metabolism. Treatment with caprylic triglyceride attenuated progression of weakness and protected spinal cord motor neuron loss in SOD1-G93A transgenic animals, significantly improving their performance even though there was no significant benefit regarding the survival of the ALS transgenic animals. We found that caprylic triglyceride significantly promoted the mitochondrial oxygen consumption rate in vivo. Our results demonstrated that caprylic triglyceride alleviates ALS-type motor impairment through restoration of energy metabolism in SOD1-G93A ALS mice, especially during the overt stage of the disease. These data indicate the feasibility of using caprylic acid as an easily administered treatment with a high impact on the quality of life of ALS patients.